Diagnosis and drugs: help or hindrance when people with learning disabilities have psychological problems? - Kroese BS; Dewhurst D; Holmes G (British Journal of Learning Disabilities, 2001)
A wide range of prevalence rates of psychiatric disorders in people with learning disabilities has been reported, and as yet, there appears to be no general consensus on how to improve the process of diagnosis in order to achieve better agreement. Distinguishing behavioural disturbance from psychiatric disorders is clearly problematic, and empirical and conceptual issues concerning the nature of these disorders brings into question the validity and reliability of psychiatric diagnosis in people with learning disabilities. Concern has been widely expressed about the high frequency with which psychotropic medication is prescribed to this client group. The present paper reviews some of the recent literature, and questions whether psychiatric diagnosis and the use of psychotropic medication are sufficiently evidence-based to be justified practice.